Structure of 15-Level Sub-Module Cascaded H-Bridge Inverter for Speed Control of AC Drive Applications - R. Uthirasamy; U. S. Ragupathy; R. Naveen (Institute of Advanced Engineering and Science, 2015)
This paper deals with the implementation of a single phase 15-level Sub-Multilevel Cascaded H-Bridge Inverter (SMCHBI) for variable speed industrial drive applications. It consists of sub-multilevel modules and H-bridge inverter configuration. Sub-multilevel switches synthesize stepped DC link voltage and current from the DC sources. H-bridge inverter switches renovate stepped DC link voltage and current into sinusoidal waveform. Compared with conventional Cascaded Multilevel Inverter (CMLI), the proposed system employs the reduced number of power switches, DC sources and gate driver requirements. The proposed system not only reduces the overall system cost but also reduces the voltage stress across the inverter switches. The proposed system does not required additional resonant soft switching circuits for Zero Voltage Switching (ZVS) of inverter. In the proposed method, variable frequency method is adopted for the speed control of industrial induction motor drives. A prototype model of 15-level SMCHB is developed and the performance of the systems is validated experimentally.